DESENTRALISASI” PENYIARAN TELEVISI DI INDONESIA DALAM KERANGKA HUKUM - Nyoman Septiari, I Gusti Ayu; Sunarto, Sunarto; Nugroho, Adi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
During the reform era, the word “decentralization” was often associated with the television broadcasting system in Indonesia. Decentralization is the transfer of responsibility from the ruler at the center to a lower unit. However, in the broadcasting industry, the concept of decentralization is also often associated with the network station system in Law Number 32 of 2002 concerning Broadcasting. This research aims to find the meaning of decentralization contained in the legal framework regarding broadcasting, namely in Law Number 32 of 2002 concerning Broadcasting and Law Number 11 of 2020 concerning Cipta Kerja. The method used in this study is Wilhelm Dilthey hermeneutic analysis through five analysis techniques, namely grammatical analysis, semantic analysis, and text meaning analysis. The word